Yoshinobu Tokugawa (ed.), The Shogun Age Exhibition, Tokyo, The Shogun Age Exhibition Executive Committee, The Tokugawa Art Museum, 1983. 279 pp. - Quintana Pali, Santiago (Estudios de Asia y África, 1985)
-